Colloidal gel elasticity arises from the packing of locally glassy clusters - Kathryn A. Whitaker (Nature Portfolio, 2019)
Colloidal gels are typically composed of solid particles dispersed in a liquid, which show some peculiar mechanic properties but their origins remain largely unsolved. Here, Whitaker et al. show that the elasticity formed via arrested phase separation arises from the packing of glassy clusters in gels.